Development of calcium phosphate/ethylene glycol dimethacrylate particles for dental applications - Natale L.C. (2019)
© 2018 Wiley Periodicals, Inc.This study describes the synthesis of dicalcium phosphate dihydrate (DCPD) particles in the presence of different ethylene glycol dimethacrylates (EGDMA, ethylene glycol/EG units: 1, 2, 3 or 4) at two monomer-to-ammonium phosphate molar ratios (1:1 and 2:1), as a strategy to develop CaP-monomer particles with improved interaction with resin matrices. Particles displaying high surface areas and organic contents were added to a photocurable BisGMA-TEGDMA resin and the resulting materials were tested for degree of conversion (DC), biaxial flexural strength (BFS), flexural modulus, and ion release. Data were subjected to one-way ANOVA or Kruskal-Wallis/Dunn test (alpha: 0.05). Functionalization with EGDMA derivatives was dependent upon the length of the spacer group and monomer concentration in the synthesis. No differences in DC were observed among materials (p > 0.05). A 39% increase in BFS was obtained with the use of particles with the highest functionalization level compared to non-functionalized particles (p < 0.001). The use of functionalized DCPD reduced flexural modulus in comparison to non-functionalized particles (p < 0.001). Calcium release was similar among materials and remained constant during the experiment, while phosphate release was higher at 7 days in comparison to the remaining weeks (p < 0.001). In conclusion, diethylene glycol dimethacrylate resulted in the highest functionalization levels and the highest BFS among DCPD-containing materials. Ion release was not affected by functionalization. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2018. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 708–715, 2019.